Manajemen SDM Dalam Prespektif Ekonomi Islam Dengan Adanya Peranan IPTEK - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Islam is one of the religions embraced by the majority of Indonesia's population, which has given color to every aspect of its adherents' lives. Starting in terms of religion, politics, social and economics. The conventional economic view places worldliness alone, not yet looking at its spiritual needs. So employees are only the object of the company and are not subject to the company. With the application of Islamic Human Resource Management, employees will submit to the company so that they can actively participate for the company's progress. Manpower or Human Resources, is a factor of production that has a big meaning. Because all natural wealth is useless if it is not exploited by humans. Therefore every company should pay attention to HR as one of the factors of production. The Qur'an has given more attention to humans, this can be seen from the passage in the verse in the letter An Najm. (Afzalur Rahman, 1995), which means: